The Moderation Role of Subjective Norm on Apple iPhone Purchase Intention: A Study on Generation Z Consumers in Indonesia - Elvira Benita; Geraldy Pratama Teguh; Adelina Proboyo (Master of Management, School of Business and Management, Petra Christian University, 2023)
With the widespread adoption of digital technology and the emergence of various smartphone brands worldwide, this research explores how these brands should adapt to the current consumer demands, particularly in a developing country like Indonesia. Gen Z has played a significant role among other generations in the Indonesian smartphone market, particularly favoring luxury brands like the Apple iPhone. Given the limited existing research on luxury consumption behavior in this market, this study aims to investigate the factors influencing the purchase intentions of Indonesian Gen Z consumers towards Apple iPhones. The research will discuss the significance of attitude, subjective norms, and perceived behavioral control in shaping consumer purchase intentions. Eighty responses were gathered from Generation Z who knew about the Apple iPhone and live in Indonesia. The study will use PLS-SEM to prove the research hypotheses using a quantitative approach with a simple random sampling method. The findings of this study highlight the pivotal role of subjective norms as the primary determinant of purchase intentions for Apple iPhone products. Furthermore, the subjective norm moderates the relationship between attitude and perceived behavioral control on purchase intentions.